Effect of Menopausal Hormonal Therapy on Cardiovascular Disease Risk Reduction in Women with Menopausal Condition: A Systematic Review and Meta-Analysis - Ferdinand Umbu Pati; Pande Made Dwijayasa (Asian Journal of Health Research, 2025)
Introduction: Women with menopausal conditions are more likely to cardiovascular illness compared to women without menopausal problems. Menopausal Hormone Therapy (MHT) has been proposed to lowers the risk of cardiovascular disease events. However, current proof of the utility of this therapy is still needed.    Material and Methods: A systematic search was conducted in PubMed, Cochrane Library, and Science Direct were searched for RCTs, as well as cohort or case-control research that evaluated the impact of monitoring on the incidence of cardiovascular diseases in patients undergoing hormone replacement therapy. Data were analyzed using a fixed/random effect model based on using heterogeneity to evaluate odds ratios (ORs) and 95% CIs, and calculated through the Inverse Variance method.    Results: Four RCTs involving 8,198 patients on MHT and compared with 8,249 control patients met the inclusion criteria. The pooled analysis showed no significant reduction in the risk of cardiovascular disease events among women treated with MHT compared with placebo (OR = 0.98; 95% CI 0.88–1.09; p = 0.72). There was no statistical evidence of heterogeneity across studies (I² = 0%, p = 0.50). All studies were assessed as a low overall risk of bias.    Conclusion: Six of seven studies found no difference in disease‐free or overall survival between MIS and open RH. One study reported worse outcomes with RRH among patients with FIGO IIB disease and multi‐agent NACT (HR 2.5–3.0; p<0.05), suggesting risk in higher‐stage, heavily pretreated cases. Overall, robotic‐assisted RH appears to be a safe and effective alternative to open surgery for appropriately selected FIGO IB₂–IIA₂ cervical cancer patients after NACT.